To multiply the polynomial expressions \( (2x^2 - 3)(x + 5) \), we will use the distributive property (also known as the FOIL method for binomials).
Here’s the breakdown of the multiplication:
-
Distribute \(2x^2\):
- \(2x^2 \cdot x = 2x^3\)
- \(2x^2 \cdot 5 = 10x^2\)
-
Distribute \(-3\):
- \(-3 \cdot x = -3x\)
- \(-3 \cdot 5 = -15\)
Now, we combine all the results:
\[ 2x^3 + 10x^2 - 3x - 15 \]
Thus, the final answer is:
\[ 2x^3 + 10x^2 - 3x - 15 \]
So the correct response is:
2x^3 + 10x^2 - 3x - 15.